PENGARUH METODE HERMENEUTIK TERHADAP PENINGKATAN PEMAHAMAN NILAI-NILAI BUDAYA SISWA KELAS VII SMP LTI IGM PALEMBANG - Nadya, Nyayu Lulu (JURNAL DIDASCEIN BAHASA, 2017)
ABSTRACT: The problem in the research is whether the hermeneutic method could increase the students‘ understanding in cultural values at SMP LTI IGM Palembang. It aims to find out whether the hermeneutic method could or could not increase the students‘ understanding in cultural values. The reserach used pretest-posttest control group design. In experiment class, the mean value in pretest was 58 and the posttest score was 78 with gain score 20. Kn control class, the mean value in pretest was 57 and the posttest score was 74 with gain score 17. After evaluation, the mean value in the posttest of students‘ results in understanding the shortsory text, both classes got significant value 0,000 which is less than significant alpha 0,05. It can be concluded that the hermeneutic method could increase the students‘ understanding in cultural values through undertanding local shortstories in Sumatera Selatan. Keywords: hermeneutic method, the understanding of cultural values, students of SMP LTI IGM Palembang class VII.